Two new species of Pezothrips (Thysanoptera, Thripidae) in Japan and Europe, with designation of lectotype of type species - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2020)
Pezothrips nadeshiko n. sp. is described from Dianthus superbus var. longicalycinus at Honshu, Japan and P. pelikani n. sp. is described from Czech Republic. A lectotype is designated for P. frontalis (Uzel), the type species of this genus, and this species is re-described. An illustrated identification key to the world species of Pezothrips is also provided.